ANALISIS COLLABORATIVE GOVERNANCE DALAM PENGUATAN KEBIJAKAN PROTEKSI LINGKUNGAN HIDUP MENUJU SMART REGENCY DI KABUPATEN GRESIK - Yendra Erison; Alif Firdaus Zamzam; Ahmad Afandi; Suci Indah Sari (Journal Publicuho, 2025)
This research aims to analyse the collaborative governance model in strengthening environmental protection policies as the foundation for the transformation of Gresik Regency towards a Smart Regency. Using a qualitative case study approach, data were collected through observation, in-depth interviews, Focus Group Discussions (FGD), and documentation of key actors such as the Environmental Service, PT Petrokimia Gresik, and civil society organisations. The research results show that the implementation of collaborative governance in Gresik has formed a pattern of collaboration involving the government, industry and civil society sectors, although it still faces challenges in the form of inequality of participation and weak deliberative space. Regional governments, through DLH, act as facilitators of adaptive environmental policies, while the industrial sector is starting to adopt a co-design approach in social responsibility programs. Civil society organisations such as Asbag and Pokdarling also encourage participatory public supervision and education. However, the collaboration that occurs is still more procedural than substantive. This research recommends the need to improve the design of environmental governance that is inclusive and transparent, where each actor has an equal position in policy formulation, implementation and evaluation. Only through parallel synergy can the ideals of Gresik as a Smart Regency based on a smart environment be truly realised sustainably.